A rare case of lateral pontine syndrome-Marie Foix syndrome - Regmi, Pradeep Raj; Amatya, Isha (Journal of Patan Academy of Health Sciences, 2021)
Lateral pontine syndrome or Marie Foix Alajouanine syndrome refers to the brainstem stroke syndrome involving lateral pons due to the infarction in the distribution of the anterior inferior cerebellar artery. It involves the lateral inferior part of the pons, middle cerebellar peduncle, and floccular region. Computed Tomography (CT) is less sensitive in brainstem infarction than  Magnetic Resonance Imaging (MRI). With the introduction of MRI, it is possible to precisely locate the brainstem infarcts. We present a case with a typical clinical picture of brainstem stroke with radiological findings consistent with the lateral pontine syndrome. Proper correlation with the clinical picture and radiological findings is important for the diagnosis of brainstem infarctions.